Crossed cerebellar diaschisis on 18F-FDG PET: Frequency across neurodegenerative syndromes and association with 11C-PIB and 18F-Flortaucipir. Issue 9 (September 2021) - Provost, Karine; La Joie, Renaud; Strom, Amelia; Iaccarino, Leonardo; Edwards, Lauren; Mellinger, Taylor J; Pham, Julie; Baker, Suzanne L; Miller, Bruce L; Jagust, William J; Rabinovici, Gil D
We used 18 F-FDG-PET to investigate the frequency of crossed cerebellar diaschisis (CCD) in 197 patients with various syndromes associated with neurodegenerative diseases. In a subset of 117 patients, we studied relationships between CCD and cortical asymmetry of Alzheimer's pathology (β-amyloid ( 11 C-PIB) and tau ( 18 F-Flortaucipir)). PET images were processed using MRIs to derive parametric SUVR images and define regions of interest. Indices of asymmetry were calculated in the cerebral cortex, basal ganglia and cerebellar cortex. Across all patients, cerebellar 18 F-FDG asymmetry was associated with reverse asymmetry of 18 F-FDG in the cerebral cortex (especially frontal and parietal areas) and basal ganglia. Based on our operational definition (cerebellar asymmetry >3% with contralateral supratentorial hypometabolism), significant CCD was present in 47/197 (24%) patients and was most frequent in corticobasal syndrome and semantic and logopenic variants of primary progressive aphasia. In β-amyloid-positive patients, mediation analyses showed that 18 F-Flortaucipir cortical asymmetry was associated with cerebellar 18 F-FDG asymmetry, but that cortical 18 F-FDG asymmetry mediated this relationship. Analysis of 18 F-FDG-SUVR values suggested that CCD might also occur in the absence of frank cerebellar 18 F-FDG asymmetry due to symmetrical supratentorial degeneration resulting in a bilateral diaschisis process.